The Effect of Poppy Oil on Egg Production and Calcium Metabolism in Japanese Quail - Csaba Szabó; Xénia Ozsváth; Brigitta Csernus; Gabriella Gulyás; Márta Horváth; Levente Czeglédi; János Oláh; Nafiatur Rizqoh; Gabriele Achille; János Posta (Animals)
Consumers tend to favor natural dietary supplements to improve their health. However, vendors rarely cite scientific evidence to justify these claims. In the case of poppy oil, it is often mentioned as having a positive effect on Ca metabolism-related disorders, but no proof has been provided. Therefore, the aim of our trial was to test the possible effect of poppy oil on calcium metabolism using Japanese quail layers as a model animal. A total of 120 four-week-old quail were divided into three dietary treatments (four cages per treatment, with ten birds in each cage): a control group (using sunflower oil as the energy source in the diet), 0.5%, and 1% poppy oil supplementation (replacing sunflower oil). Egg production, eggshell thickness, eggshell strength, and egg yolk color were investigated. Ca retention was determined using the acid-insoluble ash method. At the end of the experiment, two birds per cage were sacrificed, and uterus and jejunum samples were collected for gene expression analyses. Poppy oil supplementation improved egg production in terms of intensity, egg weight, and eggmass production. The thickness and eggshell strength decreased when 1% poppy oil was fed to the animals, while Ca retention improved. Poppy oil supplementation increased the expression of Ca transporter genes (CALB1, SLC8A1, and SLC26A9) in the uterus and ITPR1 in the jejunum. Our results indicate a possible effect of poppy oil on Ca metabolism. Further studies are needed to identify the active compound and to understand the mode of action.